1988
DOI: 10.1104/pp.88.2.333
|View full text |Cite
|
Sign up to set email alerts
|

Oats Tolerant of Pseudomonas syringae pv. tabaci Contain Tabtoxinine-β-Lactam-Insensitive Leaf Glutamine Synthetases

Abstract: (19,29) and for reassimilating the ammonia released by photorespiration (9). In this latter function, GS can be viewed as an ammonia detoxification mechanism (7). It is the loss of this detoxification function of GS in P. syringae pv. tabaci-infected leaves that results in the accumulation of millimolar concentrations ofammonia and the subsequent and characteristic chlorosis (6,8,27 We report that plants tolerant to P. syringae pv. tabaci do not utilize any of the first four mechanisms listed above, but rather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1991
1991
2004
2004

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Although, GS polypeptide levels increase in root and leaf tissues of both SC and TC oats, only the leaf GS in TC plants remains catalyticaly active. Ion-exchange chromatography of leaf GS from TC plants has revealed that both GSI and GS2 isoforms retained activity (data not shown) and earlier in vitro inactivation studies have shown that both forms of leaf GS in ' TC plants are resistant to inactivation by TKL (Knight et al, 1988). A 43% increase in specific activity of leaf GS in TC oats over TUC oats is not in accord with the dramatic increase in levels of GS polypeptide indicating that not all the GS protein in TC oat leaves is fully active.…”
Section: Changes In Gs Activity Upon Rhizosphere Infestation Bymentioning
confidence: 86%
See 3 more Smart Citations
“…Although, GS polypeptide levels increase in root and leaf tissues of both SC and TC oats, only the leaf GS in TC plants remains catalyticaly active. Ion-exchange chromatography of leaf GS from TC plants has revealed that both GSI and GS2 isoforms retained activity (data not shown) and earlier in vitro inactivation studies have shown that both forms of leaf GS in ' TC plants are resistant to inactivation by TKL (Knight et al, 1988). A 43% increase in specific activity of leaf GS in TC oats over TUC oats is not in accord with the dramatic increase in levels of GS polypeptide indicating that not all the GS protein in TC oat leaves is fully active.…”
Section: Changes In Gs Activity Upon Rhizosphere Infestation Bymentioning
confidence: 86%
“…In vitro inactivation studies with TBL reveals that GS from 'TC leaf tissue, partially purified through ion-exchange chromatography, will lose 15 to 20% of its activity. After this initial loss of activity this GS becomes resistant to further inactivation by TBL (Knight et al, 1988). A 15 to 20 % decrease in activity could represent a limited 'TBL-GS interaction where TBL could inactivate 1 or 2 active sites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is considerable natural variation between species in sensitivity to glufosinate, and this variation does not appear to be based on differential sensitivity to GS (Ridley and McNally, 1985). Lines of oat that are insensitive to the GS-inhibiting glufosinate analog, tabtoxin, have a tabtoxin-resistant GS isozyme (Knight et al, 1988); however, no plants with glufosinate-resistant GS have been reported.…”
Section: Modes Of Action and Resistancementioning
confidence: 99%